BOOK REVIEW: THE HISTORY OF CULTURAL POLICY IN INDONESIA 1900s-2000s - Wildan Sena Utama (Humaniora, 2016)
This book investigates how culture, particularly national culture, in Indonesia has been shaped by the government policies from the Dutch colonial period in 1900s to the Reformation era in 2000s. It is an attempt to show the relationship between the state and culture around the process of production, circulation, regulation and reception of cultural policy through different regimes. Although this book discusses government policy, the author has realized that the book needs to overcome contradictions and confusions of cultural discourse by incorporating people as explanatory element. Many aspect of culturality may be influenced by the state, but according to Jones, “it is a field that is not stable and easy to shift that facilitates resistance, and is able to turn against the state, market and other institutions” (p. 31). Jones employs two postcolonial cultural policy tools to review the history of cultural policy in Indonesia: authoritarian cultural policy and command culture. The first means that the state has assumption if majority of citizen do not have capability to inspirit a responsible citizenship and need a state’s direction in the choice of their culture. On the contrary, command culture shows that the cultural idea that is planned in fact always been placing the state as center in planning, creating policy and revising cultural practice.